Phase evolutions and electrical properties in BaTiO3-BaFe0.5Nb0.5O3ceramics - U. Intatha (2018)
In this work, BaFe0.5Nb0.5O3(BFN) was added to BaTiO3(BT) to form the solid solution. The investigation of phase evolution, physical properties and electrical properties of the binary system (l-x)BT-xBFN where x = 0, 0.2, 0.4 and 0.6 was carried out. The BT and BFN powders were prepared separately using a calcination technique with optimum calcinations temperature for producing both BT and BFN powders. XRD results revealed that the BT-BFN ceramics with BFN content of x less than 0.4 contain the ferroelectric tetragonal perovskite phase whereas the composition with BFN content of x = 0.6 changes symmety to the cubic phase. From the evidences including phases, microstructures and ferroelectric and dielectric data of the BT-BFN ceramics, it is inferred that the morphotropic phase boundary occurs around the composition ox = 0.4. © 2009 American Institute of Physics.